Enhancing Primary Education through Digital Learning Platforms: A Comprehensive Review - Selirowangi, Nisaul Barokati (EDUCATIO : Journal of Education, 2021)
The research aims to thoroughly examine the ways in which digital learning platforms contribute to the improvement of primary education. Employing a comprehensive review approach, the study assesses various facets, including teaching methodologies, student engagement, and overall educational outcomes influenced by the integration of digital tools. The methodology involves a systematic analysis of existing literature and research in the field of primary education and digital learning platforms. The results showcase the multifaceted positive impacts of these platforms on creating interactive learning environments and improving educational quality. Educators, policymakers, and stakeholders will find this abstract valuable for gaining insights into the potential benefits and challenges associated with leveraging digital learning platforms to enhance primary education.